Radiation attenuation and mechanical reinforcement of Eu/Gd co-doped zinc borotellurite glass system - Sani, Aliyu; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Abdul Karim, Muhammad Khalis; Loh, Loh Zhi Wei (Elsevier, 2026)
This study examines the mechanical and radiation-shielding characteristics of Eu2O3:Gd2O3 co-doped zinc Boro-tellurite glass produced by the standard melt-quenching method. XRD and FTIR investigations established an amorphous matrix exhibiting an incremental structural transformation of non-bridging oxygens (NBOs). The density and molar volume increased due to the elevated atomic number of rare-earth oxides, resulting in enhanced material strength attributed to the rise in Young's and shear modulus from (81.15 to 90.11 GPa), and (30.06 to 39.07 GPa) respectively, while Poisson's ratio reduced from (0.35 to 0.15). The direct and indirect bandgaps decreased from (3.42 to 3.20 eV) and from (3.11 to 3.03 eV), respectively, and Urbach energy varies from (2.83 to 2.92 eV), while the refractive index ranges from (2.08 to 2.11), ensuring the structural integrity of the produced glass. The Phy-X/PSD results demonstrated an improved attenuation profile, Mass attenuation coefficient (MAC) increasing from 0.188 to 0.224 cm²/g, indicating transitions coming from photoelectric effect, Compton scattering and pair production. Additionally, low-energy attenuation was found to be superior, as shown by the reduction of the half-value layer (HVL) from (0.90 to 0.71 cm), and the effective atomic number (Zeff) popping from approximately (23 to 48). Our findings concurrently characterized the EG5 formulation as an optimized, lead-free option, validating Eu3+/Gd3+ co-doping as an outstanding method that yields mechanically resilient, transparent, and highly effective shielding applications.